Who gain and lose from the minimum wage policy? - Saari, Mohd Yusof; Hassan, Azman; Said, Rusmawati (Penerbit Universiti Kebangsaan Malaysia, 2013)
This study examines the effectiveness of the minimum wage as a mechanism for income redistribution among major ethnic groups in Malaysia. Taking into consideration the benefits and costs of minimum wage, the results show that the wage policy potentially boosts the incomes of ethnic Indians and ethnic Malays, whereas the wage policy marginally affects ethnic Chinese. The estimates also do not provide strong support for the notion that minimum wage legislation in Malaysia is likely to be an effective policy for income redistribution. The effectiveness of the minimum wage legislation is constrained by its limitation to account for informal sector workers.